In Silico Study on Testing Antidiabetic Compounds Candidate from Azaphilone Mold Monascus sp. - Hilman Fitriaji S P; Khofi Siti Mukhaufillah; Lina Rahmawati Rizkuloh; Anna Yuliana (Microbiology Indonesia, 2020)
Monascus sp. is a mold that is used for rice fermentation so that the brown rice is produced (Red Mold Rice) or Angkak. This rice has long been used on Asian food and traditional medicine. Angkak contains many bioactive compounds, including monakolin which is potentially to be used as nutraceutical. Monascus sp. produced pigments include yellow (Ankaflavin, Monaskin), Orange (Rubropunktatin, Monaskorubrin) and Red (Rubropunktamin, monaskorubramin) which have various biological activities. The purpose of the study was to know the pigments of the Monascus sp. as a compound antidiabetic candidate. This includes the Azaphilone Kapang Monascus sp. derivative compound In Silico. The test compound consists of 57 compounds of Monascus sp. Glycogen Fosforilase used as an antidiabetic receptor. Ligan preparation is drawn using ChemDraw software then with Marvin Sketch done Protonasi. Testing Drug Scan (Screening ligand based Drug likeness). The preparation of receptors by downloading antidiabetic receptors in Protein Data Bank (GDP). The ADME study was conducted with PreADMET web-based software. Validate the docking method and molecular tethering using the Autodock software 4.2.6. Drugscan test results on compounds Isolate MPs4 have qualified grades in all parameters such as molecular weight, proton donor, proton acceptor, log p and molar refractory. The results of the ADME test in the compound Isolate MPs4 have a qualified value in all parameters Caco-2, HIA (Human Intestinal Absorption), as well as in the PPB (Protein Plasma Binding). The result of the docking test in the Isolate compound MPs4 to be the best and qualified compound because it has a smaller affinity binding than the natural ligands and the comparator ligand (glibenclamide). The result of this research Isolate MPs4 is the candidate for new drugs antidiabetic. Keyword : Monascus sp., In silico, Azaphilone, Docking, Antidiabetic